Crystal Engineering for Achievement of Functional Materials Through Facile Intercalation of Lamella Mineral Kaolinite (Journal of Material Science and Technology Research, 2023)
Abstract: Kaolinite, a layered clay mineral, has attracted widely attention due to its versatile advantages including low cost, environmentally friendly processing and easy modification. By comparison of the wide studies of the intercalation processes of kaolinite via the replacement of diverse intercalated agents, the multiple functional properties of intercalated kaolinites are ignored as well as such kind of study is very limited. In this review, we have summarized a series of intercalated compounds of kaolinites with organic molecules or organic salts by means of a simple intercalation strategy. Additionally, their multiple functional properties (such as dielectricity, ferroelectricity and ionic conductivity) will also be mentioned.